Konsep Penebusan dalam Kitab Rut - Wassar, Sarah (Sekolah Tinggi Teologia Kerusso Indonesia, 2022)
Every believer who wants to experience God in daily life in making important and less important decisions, both consciously and unconsciously. The message that was conveyed was that a man by grace made the decision to redeem and renew a lost inheritance, and pure love removed all difficulties. The method used to explain the meaning of redemption in the book of Ruth is a literature study in the form of a literature study. Through the description of the literature review, the author finds the results of several biblical reviews of the concept of redemption in the book of Ruth.